2012
DOI: 10.1007/s10870-012-0288-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial and Cholinesterase Enzymes Inhibitory Activities of Indeno Imidazoles and X-Ray Crystal Structure of 3a,8a-Dihydroxy-1,3-diphenyl-1,3,3a,8a-tetrahydro-indeno[1,2-d]imidazole-2,8-dione

Abstract: Two indeno imidazoles have been synthesized by the reaction of ninhydrin with diphenylurea and diphenylthiourea. The structures have been determined by spectral analysis. The supramolecular behavior of 3a,8a-Dihydroxy-1,3-diphenyl-1,3,3a,8a-tetrahydro-indeno[1,2-d]imidazole-2,8-dione (1) was thoroughly analyzed and reported using X-ray single crystal technique and concepts. The presence of oxygen and nitrogen atoms led to very interesting supramolecular motifs interactions such as nitrogen-oxygen, nitrogennitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Subsequently, the same group synthesized two indeno imidazoles 209 from the reaction of ninhydrin with diphenylurea or diphenylthiourea 208 and examined their antimicrobial activities, which showed good antibacterial activity against B. subtilis and P. aeruginosa (Scheme 61). 274 However, the authors did not determine or comment on the stereochemistry of the compounds.…”
Section: Scheme 57 Synthesis Of Indeno[12-d]imidazolidin-2-iminium mentioning
confidence: 99%
“…Subsequently, the same group synthesized two indeno imidazoles 209 from the reaction of ninhydrin with diphenylurea or diphenylthiourea 208 and examined their antimicrobial activities, which showed good antibacterial activity against B. subtilis and P. aeruginosa (Scheme 61). 274 However, the authors did not determine or comment on the stereochemistry of the compounds.…”
Section: Scheme 57 Synthesis Of Indeno[12-d]imidazolidin-2-iminium mentioning
confidence: 99%
“…Our research group has been interested in designing and preparing different types of host molecules, and investigating their ability to form host-guest complexes with different guests' functionalities [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Herein, we describe the selective synthesis, structural conformation, supramolecularity, and bioactivity of the chair conformation of 4,6,10, 12,16,18,22,24-octahydroxy-2,8,14,20-tetraphenyl-resorcin[4]arene host 3 (Scheme 1) and its DMSO-H 2 O ternary inclusion system, as part of an ongoing project aiming to design, synthesize, and investigate new calix [4] arenes compounds [33,34].…”
Section: Ternary Inclusion System Of Chair Conformation 207mentioning
confidence: 99%
“…8 Our previous studies, reported synthesis, crystal structures, supramolecularity of several indenoimidazoles with antimicrobial and cholinesterase enzymes inhibitory activities. 9,20,22 The title adducts have been synthesized in minimum time (15 min) with maximum yields (95%). Nowadays, supramolecular chemists are interested in design, synthesis, and characterization of supramolecular assemblies, which have the ability to work as functional materials.…”
Section: Introductionmentioning
confidence: 99%